Steroidogenic enzymes, their related transcription factors and nuclear receptors in human sebaceous glands under normal and pathological conditions - Azmahani Abdullah
Several types of sebaceous lesions has been known to arise from sebocytes of the skin. Skin diseases involving sebaceous glands include acne and others also well known to be influenced by sex steroids. In situ or local sex steroid hormone synthesis has been known in human skin and those locally produced sex steroids could also exert their effects upon the functions of human sebaceous glands and their diseases but the details have not been yet clarified. Therefore, in this study I performed immunohistochemical analysis of steroidogenic enzymes, nuclear receptors and transcription factors in a total of 59 human skin specimens retrieved from pathology files including 22 normal skin human sebaceous glands, 12 sebaceous nevus, 12 sebaceous gland hyperplasia, 3 seceoma and 10sebaceous carcinoma. In addition, I used immortalized human SZ95 sebocytes cell lines treated with forskolin or vehicle for 3 h, 6 h, 12 h, or 24 h for in vitro analysis in order to further understand the roles of sex steroids in sebaceous glands and their disorders. In this cell model, the mRNA levels of steroidgenic enzymes and transcription factors were evaluated at each time point using quantitative RT-PCR (qPCR). Results of immunohistochemical analysis demonstrated that immunoreactivity of 3?-HSD1, CYP11A1, StAR, 5?-red1 and NGFI-B was detected in normal human sebaceous glands, with relatively lower levels of all those above in pathological sebaceous glands. The in vitro study also revealed that the expression levels of 3?-HSD1, CYP11A1, StAR, 5?-red1 and NGFI-B were all elevated by forskolin. These results all indicated that 3?-HSD1 and other steroidogenic enzymes expressed in sebaceous glands result in biologically relevant in situ androgen and progesterone suntesis and these locally produced sex steroids influence the functions of normal as well as pathological sebaceous glands of human skin.